Fast algorithm for obtaining mathematical relations for optimizing the operating mode of an electric power system - Dolbin Kirill Sergeevich (E3S Web of Conferences, 2024)
The article proposes a method for composing mathematicalexpressions by which it is possible to reduce the time for determining theparameters of flexible alternating current transmission system devices inthe operating mode of the electric power system. The problem of quasistationarityof the steady-state regime is considered, taking into account therapidity of its change. Criteria for the optimality of the regime are also putforward. The problem of optimizing the power system mode is solved byrecording various sets of target functions. The article provides in detail analgorithm for obtaining objective functions based on the theory ofsensitivity of electrical circuits. A method is also proposed for determiningthe success of choosing functional relationships and the optimal location ofdevices.